Loss of mDia1 and Fhod1 impacts platelet formation but not platelet function. (17th November 2021) - Zuidscherwoude, Malou; Haining, Elizabeth J.; Simms, Victoria A.; Watson, Stephanie; Grygielska, Beata; Hardy, Alex T.; Bacon, Andrea; Watson, Stephen P.; Thomas, Steven G.
Abstract: An organized and dynamic cytoskeleton is required for platelet formation and function. Formins are a large family of actin regulatory proteins which are also able to regulate microtubule dynamics. There are four formin family members expressed in human and mouse megakaryocytes and platelets. We have previously shown that the actin polymerization activity of formin proteins is required for cytoskeletal dynamics and platelet spreading using a small molecule inhibitor. In the current study, we analyze transgenic mouse models deficient in two of these proteins, mDia1 and Fhod1, along with a model lacking both proteins. We demonstrate that double knockout mice display macrothrombocytopenia which is due to aberrant megakaryocyte function and a small decrease in platelet lifespan. Platelet function is unaffected by the loss of these proteins. This data indicates a critical role for formins in platelet and megakaryocyte function.